ENERGY CONSERVATION PROMOTION PERFORMANCE EVALUATION DEVICE - UMAMOTO, Eiichi (2018)
[Problem] To provide a system whereby it is possible to effect a motivation for energy conservation by a comparison to other persons. [Solution] Provided is an energy conservation promotion performance evaluation device, in which: a population constituent user identification information acquisition unit comprises a population constituent group identification information acquisition means which acquires population constituent group identification information which acquires, as a collective comparison subject, a group which is identified by group identification information which identifies a group and which is configured from a plurality of instances of user identification information as comparison subjects; and an energy conservation promotion performance evaluation result acquisition unit comprises a group energy conservation promotion performance evaluation result acquisition means which acquires, as an energy conservation promotion performance evaluation result, energy consumption performance data of a group which is identified with the population constituent group identification information which has been acquired by the population constituent group identification information acquisition means, associating said energy consumption performance data with the group identification information on the basis of a retained energy conservation evaluation rule. [Problème] Fournir un système permettant de motiver à l'économie d'énergie par comparaison avec d'autres personnes. [Solution] L'invention porte sur un dispositif d'évaluation de performance de promotion d'économie d'énergie, dans lequel : une unité d'acquisition d'informations d'identification d'un utilisateur appartenant à une population comprend un moyen d'acquisition d'informations d'identification d'un groupe appartenant à une population qui acquiert des informations d'identification d'un groupe appartenant à une population qui acquiert, en tant que sujet de comparaison collectif, un groupe qui est identifié par des informations d'identification de groupe qui identifient un groupe et qui sont configurées à partir d'une pluralité d'instances d'informations d'identification d'utilisateur en tant que sujets de comparaison ; et une unité d'acquisition de résultat d'évaluation de performance de promotion d'économie d'énergie qui comprend un moyen d'acquisition de résultat d'évaluation de performance de promotion d'économie d'énergie de groupe qui acquiert, en tant que résultat d'évaluation de performance de promotion de l'économie d'énergie, des données de performance de consommation d'énergie d'un groupe qui est identifié avec les informations d'identification de groupe de constituants de population qui ont été acquises par le moyen d'acquisition d'informations d'identification de groupe constituant une population, associant lesdites données de performance de consommation d'énergie aux informations d'identification de groupe sur la base d'une règle d'évaluation d'économie d'énergie retenue. 【課題】他者との対比による省エネの動機付けを図ることが可能なシステムを提供しようとするものである。 【解決手段】前記母集団構成ユーザ識別情報取得部が、比較対象として複数のユーザ識別情報にて構成されるグループを識別するグループ識別情報にて識別されるグループを複数比較対象として取得する母集団構成グループ識別情報を取得する母集団構成グループ識別情報取得手段を有し、前記省エネ推進実績評価結果取得部が、母集団構成グループ識別情報取得手段にて取得された母集団構成グループ識別情報で識別されるグループのエネルギー消費実績データを保持されている省エネ評価ルールに基づいてグループ識別情報に関連付けて省エネ推進実績評価結果として取得するグループ省エネ推進実績評価結果取得手段を有する省エネ推進実績評価装置を提供する。